2019
DOI: 10.1007/s13595-019-0809-z
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of defoliation and water deficit on growth, water status, and mortality of black spruce (Picea mariana (Mill.) B.S.P.)

Abstract: & Key message Defoliation followed by water deficit showed time-dependent effects on plant water status and growth in black spruce (Picea mariana (Mill.) B.S.P.). Biotic stress negatively (during active defoliation by growing instars) and positively (after defoliation) affected plant water relations. However, water deficit, alone or combined with defoliation, prevails over defoliation-related stress for radial growth and sapling vitality. & Context Tree vitality is influenced by multiple factors such as insect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…Defoliation by pests during drought has been thought to reduce evapotranspiration and hence water deficit stress, thus avoiding damage due to the interaction between pests and water deficit stress (Bouzidi et al, 2019). In support of this, the interaction between climatic moisture index and defoliation by pests enhanced the growth of surviving Populus tremuloides despite the negative effect on their survival (Cortini and Comeau, 2020).…”
Section: The Effect Of Combined Biotic and Abiotic Stresses On The Grmentioning
confidence: 99%
“…Defoliation by pests during drought has been thought to reduce evapotranspiration and hence water deficit stress, thus avoiding damage due to the interaction between pests and water deficit stress (Bouzidi et al, 2019). In support of this, the interaction between climatic moisture index and defoliation by pests enhanced the growth of surviving Populus tremuloides despite the negative effect on their survival (Cortini and Comeau, 2020).…”
Section: The Effect Of Combined Biotic and Abiotic Stresses On The Grmentioning
confidence: 99%
“…A recent study showed that a 2-year defoliation increased internal water availability and reduced mortality in young trees (Bouzidi et al, 2019). Other researches indicated a significant reduction in tree-ring width only after 5-10 years of defoliation, although twig water content, supporting tree growth remained mainly stable with only a slight decrease (Candau et al, 1998;Deslauriers et al, 2015).…”
Section: Introductionmentioning
confidence: 97%
“…Seasonal change of stem dimensions in mature stands of boreal conifers has been observed during a 3-year drought (Belien et al, 2014). During a 1-year greenhouse studies in young trees repeated once, a 23-day controlled drought reduced radial growth more than a 20-days defoliation (Bouzidi et al, 2019;Deslauriers et al, 2019). To our knowledge, no attention has been paid to stem radius variation according to the level of defoliation in natural stands, which is essential given that a potential decrease in forest productivity is expected during an insect outbreak.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forest management based on short‐rotation (70–100 years) clear‐cutting is the main cause of old‐growth forest loss because these stands are harvested first and at rate greater than that of primary disturbances (Barrette et al., 2018; Bergeron et al., 2017; Martin, Boucher, et al., 2020). In the boreal regions, climate change is also expected to increase the recurrence and severity of disturbances, in particular, spruce budworm outbreaks (Bouzidi et al., 2019; De Grandpré et al., 2018; Pureswaran et al., 2019). Hence, a better understanding of the resistance and resilience of boreal old‐growth forests in eastern Canada to recurrent moderate‐severity disturbances is vital to better evaluate the projected consequences of climate change and propose alternatives to clear‐cut‐based forest management.…”
Section: Introductionmentioning
confidence: 99%